Appropriate Blood Usage and Adherence to Guidelines in Orthopaedic Patients Managed at Moi Teaching and Referral Hospital, Eldoret, Kenya - Kibiwot, Ngetich Geofrey; Ayumba, Barry R.; Cherop, Lotodo Teresa (British Journal of Healthcare and Medical Research, 2025)
Blood transfusion is required in the management of life threatening orthopaedic trauma hemorrhage. However, this practice is faced with erratic supply, increasing demand for safe blood and inappropriate transfusions which may expose patients to transfusion associated risks. Appropriate use of blood and related products as well as adherence to transfusion guidelines has been shown to ameliorate these challenges. This study set out to determine the appropriate blood and blood components usage and adherence to guidelines in orthopaedic patients managed at Moi Teaching and Referral Hospital (MTRH), Eldoret, Kenya. Descriptive cross-sectional study design was and involved 132 transfused orthopedic trauma patients, recruited by consecutive sampling, between March 2019 and January 2020. Data was collected using interviewer administered structured questionnaire. Continuous data were summarized as median (inter-quartile range) and categorical data as frequency tables and proportions. Fisher’s Exact Test was used to assess associations between categorical variables and non-parametric Kruskal-Wallis Test was used for continuous independent variables. A p value < 0.05 was considered statistically significant. The results: Males were 101 (76.5%), median age was 36 (IQR 28, 47) years, majority of the patients, 95 (72%) were referrals, 64 (48.5%) were unskilled workers and 64 (48.5%) had primary school level of education. Most of the patients, 105 (79.5%) were injured in road traffic accidents. Most patients, 105 (79.5%) and 115 (87.1%) had normal pulse rate and systolic blood pressure respectively while 77 (58.3%) had increased respiratory rate. The median pre-transfusion haemoglobin was 8.90 (IQR 7.98, 10.35) g/dl and the commonest blood group was O positive. Patients with isolated femur fractures were 62 (47.0%). Patients who underwent primary open reduction and internal fixation were 61(46.2%). Majority of the patients, 127 (96.2%) received packed red blood cells. The proportion adherent to transfusion guidelines was 16.7% [95% CI: (10.75, 24.14)]. The factors associated with adherence were pre-transfusion haemoglobin and haematocrit levels, Fisher’s Exact and Kruskal-Wallis p value being < 0.001. Mild transfusion reactions were noted in 15 (11.4%) patients. Conclusions made were that most patients were males, transfused with packed red blood cells and majority of injuries sustained were due to road traffic accidents. The level of adherence to the institutional transfusion guidelines was low at 16.7%. Factors associated with transfusion guidelines adherence were pre-transfusion haemoglobin and haematocrit levels. The recommendation was that Moi Teaching and Referral Hospital Transfusion Committee should increase transfusion guidelines awareness among clinicians in orthopaedic trauma.